(untitled) (Global Journal of Science Frontier Research, 2013)
The need for alternative sources of energy is of vital importance in the present time when the world’s non-renewable energy sources are rapidly getting depleted. The reason for this depletion is that humans are utilizing the energy at a much faster rate than is being produced. Additionally, in some cases, it is inevitable that the primary source of certain forms of energy will just get exhausted. Clearly this is a problem that requires a lot of attention and it becomes imperative that effective solutions are devised. Solar energy is one such alternative form. It is renewable, environment friendly, easily available and free of cost. One major drawback is that solar energy is available for use only during the day. Hence it becomes necessary that a way is found by which we can utilize solar energy even during the absence of the Sun. This project attempts to do just that. The objective of this project is to utilize solar energy during the day and store some of the unused energy for use at night. There are two ways in which thermal energy can be stored, the first being via the sensible heat of a material and the second being via the latent heat. Of course, it is possible that a combination of the two is also used.